2017
DOI: 10.1007/s10096-017-3040-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a peptide ELISA to discriminate vaccine-induced immunity from natural infection of hepatitis A virus in a phase IV study

Abstract: Hepatitis A virus (HAV) is a highly infectious agent that causes acute liver disease. The infection can trigger the production of antibodies against the structural and non-structural proteins of HAV. Nonetheless, vaccination with an HAV vaccine leads to the production of a primary antibody against the structural proteins. Because the non-structural proteins are only produced during active virus replication, there is no or very little antibody production against the non-structural proteins. However, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In such cases, this would have led to a misclassification and overestimation of HAV infected individuals. Such overestimation might be bypassed using specific serological methods (with HAV non-structural epitopes) which have been very recently described 50 , 51 . Thus, such a new technique could then also be implemented in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, this would have led to a misclassification and overestimation of HAV infected individuals. Such overestimation might be bypassed using specific serological methods (with HAV non-structural epitopes) which have been very recently described 50 , 51 . Thus, such a new technique could then also be implemented in a follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…200 The potential value of such a diagnostic tool was then not further investigated. Interest in this topic reemerged recently and several publications on tests using recombinant antigens [201][202][203] claim to be able to discriminate between natural infection and antibodies induced by live-attenuated or inactivated vaccines, 201,202 or to distinguish between natural infection and immunity induced by inactivated vaccines. 203 The aforementioned three studies were made with sera collections containing mainly onetime samples only.…”
Section: Infection-versus Vaccine-induced Anti-hav Antibodiesmentioning
confidence: 99%
“…Therefore, we further dissected the antibody responses against these viruses by examining protein– and peptide-level reactivity profiles. Notably, all HAV vaccines approved for use in the US are inactivated and it has been shown that antibody responses to natural infection and vaccination can be differentiated by measuring the response to nonstructural proteins, to which a response will only be generated with a natural infection (i.e., when there is virus replication and production of non-structural proteins) (42). Therefore, to examine the role of natural exposure to HAV in the observed difference in seropositivity, we mapped all enriched HAV peptides for each seropositive sample across the HAV proteome.…”
Section: Resultsmentioning
confidence: 99%